Optimasi Konsumsi Fuel Dump Truck Terhadap Pengaruh Grade Jalan Pada Aktivitas Penambangan Pada PT. Pamapersada Nusantara Kecamatan Sangatta Utara Kabupaten Kutai Timur - Mushawir Mushawir; Harjuni Hasan; Henny Magdalena (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
The grade or slope of the road in a mining activity is certainly unavoidable. In addition to naturally following topographical contours, the shape of the mining pit is carried out from a high elevation leading to the lowest elevation following the slope level and the continuity of the excavation material makes the road should be made sloping. The high or low value of the road grade in addition to affecting the speed and travel time required by the unit, of course, also affects the level of fuel consumption. PT. Pamapersada Nusantara uses a conveyance unit with the HD Komatsu 785-7 type to move overburden material. Based on the results of the analysis, in the loaded condition, grade 2% uses 0.45 liters of fuel, 5% grades 0.77 liters, 6% grades 0.89 liters, 8% grades 1.09 liters and grades . While in the unloaded condition, grade 2% uses 0.19 liters of fuel, 5% grades 0.35 liters, 6% grades 0.4 liters, 8% grades 0.47 liters and 9% grades 0. 52 liters.